OPTIMIZATION OF Zn2+ METAL ION DETECTION USING PENCIL LEAD ELECTRODE MODIFIED WITH SILVER THIN LAYER BY CYCLIC VOLTAMMETRY METHOD - Zolla Azhara (UIR Press, 2024)
Zn2+ metal ions are heavy metals that are essential for the growth and development of organisms but if the amount of zinc (Zn) in excess can be toxic and disrupt the balance of the ecosystem. This research aims to study the electrochemical response of Ag/PLE to detect Zn2+ metal ions and determine the optimum conditions of supporting electrolyte and supporting electrolyte pH for the measurement of Zn2+ metal ions. In this study, electrochemical method was used to detect Zn2+ metal ion. The electrode was modified with a thin layer of silver by electrodeposition with the cyclic voltammetry method. The results showed that Ag/PLE gave a better response than PLE in detecting Zn2+ metal ions with acetate buffer solution with pH 4 as supporting electrolyte and optimum pH.